BIOMARKERS IN SERUM, URIC ACID AS A RISK FACTOR FOR TYPE 2 DIABETES ASSOCIATED WITH HYPERTENSION - Gk, Tripathi; Sharma, Rachna; Kumar Verma, Manish; Sharma, Preeti; Kumar, Pradeep (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objectives: Uric acid (UA) is the end product of purine metabolism in humans. UA is the final oxidation product of purine catabolism and has been implicated in diabetes mellitus (DM) as well as in hyperlipidemias. Hyperuricemia can cause serious health problems including renal insufficiency. Hyperuricemia is associated with many diseases including hypertension (HTN), DM, hypertriglyceridemia, and obesity. The aim was to determine the serum UA (SUA) level in Patients of Type 2 DM with HTN. Methods: Out of 100 samples, 50 were found as cases of Type 2 diabetic with HTN, and the 50 control samples were without Type 2 diabetic HTN. Results: SUA, glycosylated hemoglobin, and low-density lipoprotein of male and female cases of Type 2 DM with HTN compared to control were (p<0.05) highly significant and also serum triglycerides and total cholesterol of both sex groups of Type 2 DM with HTN compared to control were found to be (p<0.05) highly significance. Conclusion: It is concluded from our present study that level of SUA >7.0 mg/dl were significantly seen in cases of diabetes with HTN. SUA â‰¤5.0 mg/dl was significantly seen in subjects without diabetes with HTN. Our data showed hyperuricemia and glycated hemoglobin as significant risk factors in the progression of DM, atherosclerosis, myocardial infarction, renal disorder, hypertriglyceridemia, and obesity. Further large sample size studies are needed to be done in the direction with more focused mechanistic approaches to fortify the fact. Very little is known about the relationship between UA, DM, and HTN in India. Keywords: Diabetes mellitus, Hypertension, Uric acid, Glycosylated hemoglobin, Lipid profile